Escherichia coli na cavidade oral: Frequência na creche como fator de risco - Oliveira, Ageane Monteiro [UNIFESP] (2011)
Objective: To investigate the ocurrence of Escherichia coli (E.coli) in samples of saliva in children up to 36 months after exposure to child public daycare center and home environments. Methods: We investigated the presence of E. coli, considered as an indicator of fecal contamination, in saliva samples from 141 children, 53 non-attending and 88 attending child daycare center. Two samples of each child were collected on the same day at 7:00 am and 3:00 pm and plated on MacConkey Agar for further identification of E. coli. The following characteristics of the daycare center were evaluated: attended full-time only children up to 36 months, staff training, diaper changing area and toilets only for children’s use. Results: Samples E. coli negative in the morning and positive in the afternoon were statistically associated with the condition of the child attending day care center (Odds ratio= 2.72; 95% confidence interval= 1.15/6.46). There were no statistically significant associations between gender, age over 12 months, bottle feeding, use of diaper and pacifier, and tooth brushing.Conclusion: Exposure to the daycare center environment favored the potential risk of transmission of enteropathogens, as demonstrated by the presence of E. coli in saliva, even though the daycare center provided adequate child care practices and had good hygiene condition. The method proved to be easy to sampling, non-invasive and feasible in young children. As is unknown how long E. coli can survive in oral cavity that may have prevented the finding of associations between positive samples and some risk factors depending upon the time of the sampling.